Management factors contributing to delays in cancer drug registration in South Africa - Shai, Mmatsela Lorraine (University of the Witwatersrand, Johannesburg, 2022)
One of the leading causes of sickness and early death worldwide is cancer.The cancer mortality is especially high in low and middle-income countries (LMICs). The National Medicines Regulatory Authorities (NMRAs) play an important role to ensure that drugs meet the quality, safety, and efficacy requirements made available to patients. The National regulatory authorities are also accountable for enforcing regulatory demands promptly andensuring that patients have timely access to drugs. Delays in the registration of cancer drugs will have an adverse impact on cancer patients such as poor quality of life and early death. Section 27 of the Constitution of South Africa guarantees the right to have access to health care service. The study aims to determine management factors that contribute to delays in the registration of cancer drugs. As a result, the research contributes to the theoretical body of knowledge. The study took a qualitative approach by sending out an interview schedule to 10 South African pharmaceutical companies for self-completion. Several methods were considered in determining a suitable study strategy, study design, research approach, and self-administered interview questions. These methods were implemented in order to achieve the study’s objectives. This served as a primary source of information. The interview questions were completed and uploaded for analysis using the Qualtrics XM tool. The information that was gathered showed that all of the participants have to deal with the problem of registration delays for cancer drugs. The findings could help to clarify the overall critical factors, their impact, and the relationship between the key factors and stakeholders involved in cancer drug registration. The uniqueness of this research lies in the results provided by different participants from the pharmaceutical industry and in evaluating their perspectives on these delays. The research adds significant value through its evidence based on the responses received
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Management factors; Delays; Cancer; Registration; Drug application; Regulators; Pharmaceutical Companies.; UCTD; SDG-8: Decent work and economic growth